A study to evaluate the relevance of the teaching methods used in th e English for beginners course of YWCA (Uganda) for the learners of 199 1/1992 - Ojamuge, George Dickens (Kampala : Makerere University, 1992)
Dissertation (Dip.) Adult education - Makerere University, 1992
Includes bibliographical references (p.42)
Keywords: English language -- Study and teaching (elementary) -- Uganda -- Kam pala district; Adult education -- Kampala District